Visual Perceptions Skills and its Association with Written Mathematical Communication Skills among Learning Disabilities Students in Jordan - Saida Aladwan; Worud Awamleh; Mona Qutaifan Ershed Alfayez; Hassan Rafi’ Ali Shaheen; Muna Saleem Taha Abutaha (Health Psychology Research)
# Aim